2018
DOI: 10.1136/bmj.k2644
|View full text |Cite
|
Sign up to set email alerts
|

Risks of ovarian, breast, and corpus uteri cancer in women treated with assisted reproductive technology in Great Britain, 1991-2010: data linkage study including 2.2 million person years of observation

Abstract: ObjectiveTo investigate the risks of ovarian, breast, and corpus uteri cancer in women who have had assisted reproduction.DesignLarge, population based, data linkage cohort study.Setting and participantsAll women who had assisted reproduction in Great Britain, 1991-2010, as recorded by the Human Fertilisation and Embryology Authority (HFEA).InterventionsHFEA fertility records for cohort members were linked to national cancer registrations.Main outcome measuresObserved first diagnosis of ovarian, breast, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 31 publications
1
47
0
3
Order By: Relevance
“…[10][11][12][13][14] A large British cohort study published in 2018 found no association between breast cancer and endometriosis among women receiving infertility treatment with assisted reproductive technologies. 15 In contrast, an increased incidence of breast cancer has been observed in recent study with histologically proven endometriosis. 9 The differences in the overall incidence of breast cancer between different subtypes of endometriosis were small in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[10][11][12][13][14] A large British cohort study published in 2018 found no association between breast cancer and endometriosis among women receiving infertility treatment with assisted reproductive technologies. 15 In contrast, an increased incidence of breast cancer has been observed in recent study with histologically proven endometriosis. 9 The differences in the overall incidence of breast cancer between different subtypes of endometriosis were small in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies assessing the relationship between endometriosis and breast cancer have reported conflicting results. Some recent large studies have suggested that the risk of breast cancer among endometriosis patients is increased [7][8][9] , whereas several other studies reported no such risk [10][11][12][13][14][15] Moreover, a cross-sectional study from North America found a decreased prevalence. 16 We have previously assessed the risk of gynecological and non-gynecological cancers according to the type of endometriosis.…”
Section: Accepted Articlementioning
confidence: 97%
“…However, there may be a transient increase in the incidence of breast cancer in the first year due to earlier diagnosis (Salhab et al, 2005). Williams and colleagues describe no increased risk of invasive breast cancer but increased risks of in situ breast cancer in women who have had assisted reproduction (Williams et al, 2018). In another study, Van den Belt and colleagues describe a significantly lower risk of breast cancer among women who undergoing seven or more IVF cycles compared with women who underwent one or two (hazard ratio [HR]: 0.55) (van den Belt-Dusebout et al, 2016).…”
Section: Long-term Complications After Artmentioning
confidence: 99%
“…Kessous and colleagues describe an association between IVF treatment and ovarian and uterine cancer in a study of 4000 IVF patients (Kessous et al, 2016). Williams and colleagues showed no increased risk of corpus uteri cancer but increased risks of invasive and borderline ovarian tumours in women who had assisted reproduction (Williams et al, 2018). Results suggest that ovarian tumour risks could be due to patient characteristics, rather than assisted reproduction itself, although both surveillance bias and the effect of treatment are also possibilities.…”
Section: Long-term Complications After Artmentioning
confidence: 99%
“…Several studies suggest that infertile women are at higher risk of cancer than women from the general population, particularly hormonesensitive cancers of the breast, ovaries and endometrium (Brinton et al, 1989;Rossing et al, 1994;Venn et al, 1995;Meirow and Schenker, 1996;Modan et al, 1998;Althius et al, 2005b;Rizzuto et al, 2013;Practice Committee of ASRM, 2016;Skalkidou et al, 2017;Williams et al, 2018). There is some conflicting data, however, from additional studies showing no association between infertility and risk of breast and ovarian cancer (Venn et al, 1995;Kashyap et al, 2004;Jensen et al, 2007;van den Belt-Dusebout et al, 2016).…”
Section: Introductionmentioning
confidence: 99%